Cardiopulmonary Resuscitation Training Disparities in the United States. Issue 5 (May 2017) - Blewer, Audrey L.; Ibrahim, Said A.; Leary, Marion; Dutwin, David; McNally, Bryan; Anderson, Monique L.; Morrison, Laurie J.; Aufderheide, Tom P.; Daya, Mohamud; Idris, Ahamed H.; Callaway, Clifton W.; Kudenchuk, Peter J.; et al.
Abstract : Background: Bystander cardiopulmonary resuscitation (CPR) is associated with increased survival from cardiac arrest, yet bystander CPR rates are low in many communities. The overall prevalence of CPR training in the United States and associated individual‐level disparities are unknown. We sought to measure the national prevalence of CPR training and hypothesized that older age and lower socioeconomic status would be independently associated with a lower likelihood of CPR training. Methods and Results: We administered a cross‐sectional telephone survey to a nationally representative adult sample. We assessed the demographics of individuals trained in CPR within 2 years (currently trained) and those who had been trained in CPR at some point in time (ever trained). The association of CPR training and demographic variables were tested using survey weighted logistic regression. Between September 2015 and November 2015, 9022 individuals completed the survey; 18% reported being currently trained in CPR, and 65% reported training at some point previously. For each year of increased age, the likelihood of being currently CPR trained or ever trained decreased (currently trained: odds ratio, 0.98; 95% CI, 0.97–0.99; P <0.01; ever trained: OR, 0.99; 95% CI, 0.98–0.99; P =0.04). Furthermore, there was a greater then 4‐fold difference in odds of being currently CPR trained from the 30–39 to 70–79 year old age groups (95% CI, 0.10–0.23). Factors associated with a lower likelihood of CPR training were lesser educational attainment and lower household income ( P <0.01 for each of these variables). Conclusions: A minority of respondents reported current training in CPR. Older age, lesser education, and lower income were associated with reduced likelihood of CPR training. These findings illustrate important gaps in US CPR education and suggest the need to develop tailored CPR training efforts to address this variability.